Collaborative Manufacturing: Using Real-Time Information to Support the Supply Chain - McClellan, Michael (CRC Press, 2009)
ollaborative manufacturing is an interactive process with great potential, but without the direct input of the plant floor systems information, a significant piece of the management process is not available for consideration. Collaborative Manufacturing provides guidance and examples of how and why real-time events within the plant floor management infrastructure should be an integral on-line systems link within the supply chain process. The text presents an overview of the resources planning systems, the design and management of plant data systems, including manufacturing execution systems and methods for calculating ROI when applying collaborative techniques. This professional how-to-guide will help end users understand the significant benefits of this technology and aids them in system design and implementation.